12x-6-x=6-5x-5+15x

Simple and best practice solution for 12x-6-x=6-5x-5+15x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-6-x=6-5x-5+15x equation:


Simplifying
12x + -6 + -1x = 6 + -5x + -5 + 15x

Reorder the terms:
-6 + 12x + -1x = 6 + -5x + -5 + 15x

Combine like terms: 12x + -1x = 11x
-6 + 11x = 6 + -5x + -5 + 15x

Reorder the terms:
-6 + 11x = 6 + -5 + -5x + 15x

Combine like terms: 6 + -5 = 1
-6 + 11x = 1 + -5x + 15x

Combine like terms: -5x + 15x = 10x
-6 + 11x = 1 + 10x

Solving
-6 + 11x = 1 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-6 + 11x + -10x = 1 + 10x + -10x

Combine like terms: 11x + -10x = 1x
-6 + 1x = 1 + 10x + -10x

Combine like terms: 10x + -10x = 0
-6 + 1x = 1 + 0
-6 + 1x = 1

Add '6' to each side of the equation.
-6 + 6 + 1x = 1 + 6

Combine like terms: -6 + 6 = 0
0 + 1x = 1 + 6
1x = 1 + 6

Combine like terms: 1 + 6 = 7
1x = 7

Divide each side by '1'.
x = 7

Simplifying
x = 7

See similar equations:

| 4x+16+14x+26-15x-30=0 | | 6x+9=11x+-36 | | 3x+-3=x+9 | | 3(x+2)=5(x+1)-(2x-1) | | 1/3r-20=-5 | | 3x^5-7x^4+6x^2-14x=0 | | 3(x+2)=5(x+1)-2(x-1) | | 4x-4=-5x-20 | | 40-21(3x+5)-12(3-5x)+8=0 | | 13+4(6x-5)=5(5x+2) | | 4-7=18-x | | x+40=-9 | | 4-7I=18/x | | 25x-16-9x=20+24x-10-10x | | 2t+11-4t=13 | | 12x+15=9x+15 | | 7x-(-8x+12-(24x+12)-2)=9x+62 | | 2(x+4)-12=20 | | 45.99(207.96/100)=4 | | 7x+8x+12-24x-12-2=9x+62 | | 3x-6=4x+4-13 | | 8-3h=2 | | 9x-15y=75 | | =12a(2/3+102/5) | | 39x+12=9x+62 | | 45x-20x= | | 3x-15=-3x-3 | | 2log*9(x)=log*9(8)+log*9(x-2) | | 7x-6+3x-5=8x+5-10x-4 | | 148.75=9.25(-6+t) | | 2log^9(x)=log^98+log^9(x-2) | | 27r^2+17n+72=0 |

Equations solver categories